TP9.2.13Outcomes of Emergency Groin hernia repair: 30-months experience of a tertiary care hospital. (28th October 2021) - Kumar, Dileep; Tan, Brandon; Guilbert, Michael; Elsllabi, Mohamed; Muthukumarasamy, Girivasan
Abstract: Aims: Repair of Emergency groin hernia is variable across different regions and even within same units. Mesh is increasingly used these days. We aim to evaluate peri-operative and long-term outcomes over last 30-months. Methods: Retrospective analysis of all emergency groin hernia repairs from January 2018- July 2020 in a tertiary Centre. Case notes and electronic patient records (clinical portal, PACS system etc.) used for data collection. Results: Of 89 emergency groin hernia repairs 62(69.7%) males, 32/89 (35.9%) indirect inguinal hernia and 29 (32.5%) femoral hernia. Median age 72 years (range 20-95), 74(83.1%) primary hernia and 15(16.9%) recurrent hernias. Femoral hernia was most common in females 25/27 (92.5%) in contrast 58/62 males (93.5%) had inguinal hernia. All patients, except 1(1.1%) laparoscopic, had open repair, 11/89 cases (12.3%) required bowel resection, of those 10 (90.9%) had suture repair. Additionally, 6/89 cases (6.7%) needed laparotomy. Of 68/89 (76.4%) cases who had mesh repair, 52(76.4%) were inguinal and 23.5% (16/68) femoral hernia. Only 55% femoral hernias repaired with mesh. Median LOS was 3 days (range 0-54), 6/89 cases (6.74%) had wound complications (3 wound infections, 2 haematoma and 1 fluid collection). With median 19 months (range 6-36 months) follow-up, 1(1.1%) recurrence each in both mesh and suture repair groups, no mesh infection and 2/89 (2.2%) 30-day mortality recorded. Conclusion: Mesh repair is increasingly used in emergency groin hernia repair without increased risk of mesh infection, although suture repair is still preferred in groin hernias requiring bowel resection.